Analisis Usahatani Kacang Tanah (Arachis hypogaea L) di Nagari Maninjau Kabupaten Agam - Widyan Fernanda; Rini Hakimi; Rina Sari (Jurusan Sosial Ekonomi, Fakultas Pertanian, Universitas Andalas, 2026)
This study aims to describe peanut cultivation techniques, analyze income and profits, and determine the R/C of peanut farming in Nagari Maninjau, Tanjung Raya District, Agam Regency. The method used is descriptive. The data analysis in this study is qualitative and quantitative. The sampling method used was snowball sampling, with a sample size of 30 farmers. Data was collected by direct interviews with farmers using questionnaires. The study results show differences in peanut farming in Nagari Maninjau from the theory. Farmers do not carry out balanced fertilization, land maintenance, pest and disease control, and post-harvest handling, so production is not optimal. The average income was IDR 11,044,741/Ha, and the profit was IDR 3,379,474/Ha. The revenue per cost (R/C) of peanut farming is 1.33, meaning that farmers will generate revenue from every cost expenditure of IDR 1. Farmers earn a revenue of 1.33, earning a profit of IDR 0.33.